Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content:1. Suicide causes, motives, methods of prevention and treatmentInaam Eid Mohammad Zaatrh “ Abu Zuiater”, Iyad Selim Abdul razzaq Alhallaq2. The role of the ruling elites in exacerbating ethnic, denominational discrimination and its Impact on the emergence of social movement in the second wave of the Arab Spring in SudanFarida Ezzaghari3. The quantitative assessment of water erosion in the southeast of Central Rif – MoroccoMohamed Senhaji, Mohamed Abahrour, Mostafa Hmamouchi, Youness Abahrour4. Generalization of the Fibonacci sequence, Pascal's triangle, and the binomial theoremMohammed Elsmani Abdelrahman5. Related Strategies and Practices of News Institutions in Dealing with News Text Addressing Issues of Islamists (Study Case: BBC World and Al-Arabiya 2022)Hind Saad Alrashid
Keywords: Arab Journal of Sciences & Research Publishing